Cash pooling : techniques, obstacles and alternative solutions (2011)
Centralizing companies’ treasury and implementing a cash pooling system allows groups to optimize their cash management and to reduce costs. Through a cash pooling system companies can centralize on a daily basis the treasury surpluses and needs of the different subsidiaries. It is constantly evolving and even if it is being more used in companies, it is still considered a tough and complex process. Given the current situation (increasing tendency of globalized companies and generalized difficult economic environment) cash management role becomes more emphatic and more pressure is exercised to treasury teams; this is when cash pooling appears as an effective alternative not only to alleviate possible problems (e.g. liquidity, reporting or controlling) but to improve processes.